Self-care intervention to reduce oral candidiasis recurrences in HIV-seropositive persons: a pilot study - Hilton JF, MacPhail LA, Pascasio L, Sroussi HY, Cheikh B, LaBao ME, Malvin K, (Blackwell Synergy, 2004)
This single-blind randomized controlled pilot study evaluated the efficacy of a behavioral intervention program, PRO-SELF: Candidiasis, to reduce time to recurrence of oral candidiasis over 6 months in susceptible HIV-seropositive persons. The intervention involved instruction by dentists on improving oral hygiene, minimizing sugar intake, and self-diagnosing candidiasis.